Theological Reflections on the Pandemic - Marzouk, Safwat (Interpretation, 2023)
As a response to communities of faith that are trying to make sense of the COVID-19 pandemic, this essay explores biblical traditions about “chaos” represented by primordial waters and monsters that disturb the created order. The essay begins with a summary of three biblical portrayals of chaos: chaos as integral to the created world, chaos as mystery, and chaos intensified by human rebellion. The discussion then weighs divine sovereignty and human responsibility and accepts that chaos is a part of life that challenges humans to work to make this world a better place. Among many possible responses to the chaos presented by the pandemic, this article will focus on lament, fear and trust, and repentance.